PENERAPAN MEDIA KOLASE UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK KELOMPOK A TK FADILAH KOTA PAREPARE - Halifah, Syarifah (IAIN Parepare, 2024)
This research aiims to improve the fine motor skils of young children in group A of Fadilah Kindergarten, Parepare City. Results of initial observations: Researchers saw that several children were unable to control hand movements using small muscles. This research uses qualitative research methods with a descriptiv aproach. Data collection techniques use observation, interviews, and documentation. The research instrument used Child Development Achievement Level Standards (STTPA). The results of the research show that some children are not yet able to coordinate their fine muscle hand movements. After researchers applied collage media, children who could not initially coordinate their eyes and hands experienced an increase in their ability to coordinate hand movements involving their small muscles. From the results of this activity, the researchers concluded that there was an increase in children's fine motor development through collage games, where all sub-indicators of the assessment increased.